Theoretical Study on Understanding the Effects of Core Structure and Energy Level Tuning on Efficiency of Nonfullerene Acceptors in Organic Solar Cells. Issue 8 (11th July 2021) - Joseph, Saju; Ravva, Mahesh Kumar; Davis, Binny A; Thomas, Sabu; Kalarikkal, Nandakumar
Abstract: Nonfullerene acceptors (NFAs) are a new focus in organic photovoltaics (OPVs), and continue to progress upon the drawbacks of many fullerene‐based electron acceptors. The aim of this work is to identify some important parameters that influence the efficiency of NF‐acceptors in OPVs. These results provide an enhanced understanding of the effect of the NFAs core structure (electron rich/poor group) on the photophysical and optoelectronic properties. In addition, the effect of the small ΔLUMO value (the subtle difference in energy between LUMO+1 and LUMO orbitals of NFAs; LUMO=lowest unoccupied molecular orbitals) on ultrafast charge transfer and charge separation processes in OPVs, recently identified as a key factor for all top rated high performing NFAs, is studied. So far, ΔLUMO‐based theoretical studies are limited to individual NFAs; here, for the first time, the authors have extended to the respective donor/acceptor complexes as well. Finally, based on the first‐principles density functional theory calculations with the seven reported NFAs, PC 61 BM, P3HT, and the seven newly modeled donor–acceptor complexes, this study sheds light on important factors that will provide trends and guidelines for further rational design of more efficient NF‐acceptors for OPVs. Abstract : The important parameters influencing the efficiency of nonfullerene acceptors (NFAs) in organic photovoltaics, predicted using quantum chemistry calculations, are reported. The calculated results demonstrate that the NFA's core structure (electron rich/poor group) as well as NFA with small ΔLUMO (the subtle difference in energy between LUMO+1 and LUMO orbitals; LUMO=lowest unoccupied molecular orbitals) accelerates the charge separation, open circuit voltage, and overall efficiency.